The influence of stratification by motor-vehicle ownership on the impact of built environment factors in Indian cities. (January 2017) - Rahul, T.M.; Verma, Ashish
Abstract: Development of compact cities, many contend, aids in the promotion of sustainable modes (public transit, walking and cycling). But the studies done until now have inadequately represented the effect of socio-economic stratification on the relationship between built environment factors and non-motorized transport (NMT) mode choice, which is important in context of a developing country like India. The present study, done in the city of Bangalore, analyzes the influence of built environment factors –density and diversity - on the mode choice and trip distance for the two segments: respondents owning at least one personal vehicle and respondents not owning any personal vehicle. The built environment factors are analyzed for their marginal effects in the presence of various socio-demographic and alternate specific attributes. The results of the built environment factors for the vehicle non-owning group highlighted the requirement of a policy framework to reduce their trip distance by controlling their employment and housing location. The gender of a commuter had a significant effect on the choice of modes, and the results that females had a higher likelihood of using NMT compared with males contradicted the results in other cities. Also, the trip distance model determined that females preferred a shorter walking distance compared with males. Further, the study determined the need for a well-planned, inclusive and coordinated land-use and transport control strategies in the future. Highlights: Effect of socio-economic stratification on built environment influence. Urban India has large number of vehicle non-owners who belong to low-income group. Modeled NMT mode choice of respondents owning and not owning private vehicles. Policies required to improve the accessibility of low-income group to jobs. Females have a positive disposition towards NMT compared with males.